Claiming Feminist Space in Korean Cyberterritory - Choi, Yisook; Steiner, Linda; Kim, Sooah (Javnost-The Public, 2006)
This paper analyses two Korean feminist webzines. We use the two cases to investigate the conditions under which feminist online media can survive, express alternative and feminist voices, and build a feminist community. The research is based on interviews with people involved in the zines’ production, and on qualitative and quantitative analyses of the zines’ contents, with particular attention to spaces provided for audience interactions. We conclude that Dalara and Unninet play a significant role in enlarging the meaningful space for women in virtual world and helping to build a women’s network that is both technologically sophisticated and politicized but also comfortable and familiar. Readers apparently feel bound to one another, with mutual responsibilities and reciprocal duties. But Dalara and Unninet did not escape the constraints imposed on traditional women’s alternative media. Time, energy, and money – always limited resources – remain intractable issues even for online communities.